The Shape of the Land : Topography & Landscape Architecture. - Treib, Marc (Novato : Oro Editions, 2022)
Essays by Daniels, Stephen ; Descombes, Georges ; Geuze, Adriaan ; Guthrie, Jennifer ; John-Alder, Kathleen ; Kucan, Ana ; Kullmann, Karl ; Lameiras, José Miquel ; Meyer, David ; Rosenberg, Elissa ; Smets, Bas ; Solano, Laura ; Treib, Marc
boek